Technology Acceptance of Cadastral Mapping System: A Demographic Study Among Land Branch Officers in Lands and Surveys Department of Sarawak / Mohamad Arif Abdullah - Abdullah, Mohamad Arif (2015)
This research analyzed the acceptance of employees towards system using a new model of motivation. The new model, called the motivation and acceptance model (MAM), was introduced and developed by Siegel (2008), inspired by the technology acceptance model and the commitment and necessary effort model of motivation.